(untitled) (Bangladesh Journal of Infectious Diseases, 2017)
Background: Wound infection is an important issue for surgical operations. Objective: The purpose of the present study was to measure the rate of wound infection of non-traumatic emergency laparotomy cases. Methodology: This descriptive cohort study was carried out in the Department of Surgery at Dhaka Medical College, Dhaka from July 1997 to June 1998 for a period of 1(one) year. Pre-operative patients were carefully assessed for any host factors related to wound infection. Different per-operative factors that influence the rate of postoperative wound infection were also analyzed. Swabs were taken from the suspected postoperative wound and sent for bacteriological examination. Result: In this series, 100 cases of emergency laparotomies (non-traumatic) were analyzed. Bacteriological examination showed positive culture in most of the cases but three were found to be negative result. Wound infection rate of specific type of operation were 12.5%, 20.0%, 6.6%, 40.0%, 40.0%, 33.3%, 50.0%, 50.0%, and 100.0% in duodenal ulcer perforation, pre-pyloric and gastric ulcer perforation, acute appendicitis, burst appendix, ileal perforation, small intestinal obstruction due to bands and adhesions, volvulus of sigmoid colon, obstructed inguinal hernia, generalized peritonitis due to puerperal sepsis respectively. The overall surgical wound infection rate was 19.0%. Conclusion: The rate of wound infection of non-traumatic emergency laparotomy cases are frequently found in a well-established tertiary care teaching hospital. Bangladesh J Infect Dis 2015;2(1):9-12